Sistem Informasi Manajemen Kepegawaian Berbasis Web pada Kantor BKPSDM Kabupaten Sumba Tengah - Marlince Mesa; Ardiyanto Dapadeda; Dian Fransiska Ledi (Yayasan Kawanad, 2026)
The BKPSDM of Central Sumba Regency previously managed all employee data through manual processes, producing administrative inefficiencies, redundancy risks, and persistent reporting delays. A web-based Personnel Management Information System (SIMPEG) was developed and deployed to digitize civil servant data management within the agency. The R&D methodology guided the study; data were gathered through in-depth interviews and direct field observation. The system was built using PHP, a MySQL database, and the Bootstrap framework for a responsive interface. The resulting application combines employee data CRUD operations, role-based access control, and personnel statistics visualization via Chart.js. Beyond automating report generation, the system provides an interactive dashboard supporting real-time analysis of employee composition. Strict relational database design ensures referential integrity across all data entities, while PHP session management enforces authentication at every access point. Field trials confirmed that all ten tested functions performed as expected. This deployment measurably advances administrative governance modernization, improves data accuracy, and accelerates strategic decision-making for regional leadership — marking concrete progress toward Central Sumba Regency's Electronic-Based Government System (SPBE) targets.